Ideology: Factors of Conflict and Failure in the Middle East - Hasbi Jabbar (International Journal of Science and Society, 2023)
The following article discusses how Western ideology is a major factor in the occurrence of conflict and state failure in the Middle East. In this article, the author examines the perspective of ideological hegemony. The ideology destroys the political and economic system that is at the root of social inequalities, thus accelerating the outbreak of conflict in the Middle East. The author cites Syria and Libya as examples to prove the driving factors of the conflict. The author argues that the main cause of the conflict in the Middle East is the influence of Western ideology which has not been accepted by both those in power and society, which has led to divisions and even wars. Democracy is an accepted model in many countries that cannot be applied in the Middle East. The author also criticizes the failure of the implementation of democracy and the liberal economy in the Middle East.